1988
DOI: 10.1017/s0022215100105444
|View full text |Cite
|
Sign up to set email alerts
|

Medical management of active chronic otitis media: A controlled study

Abstract: About 2 per cent of adults have active chronic otitis media, the majority being managed by medical means. Previous controlled studies have been unable to show benefit from any medication, including systemic or topical antibiotics, but the effect of the addition of topical steroids to the latter has never been evaluated.One hundred and sixty three adults with active chronic otitis media were randomly allocated to receive either antibiotic/steroid ear drops or placebo therapy over a 4–6 week period. Fifty-two pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 8 publications
1
36
0
1
Order By: Relevance
“…This was a limitation as almost all our patients had admitted to have used such medications. But quite interestingly, some investigators have found little or no evidence that topical antibiotics can cause significant SNHL in humans [19].…”
Section: Discussionmentioning
confidence: 99%
“…This was a limitation as almost all our patients had admitted to have used such medications. But quite interestingly, some investigators have found little or no evidence that topical antibiotics can cause significant SNHL in humans [19].…”
Section: Discussionmentioning
confidence: 99%
“…Concerns have been expressed regarding the use of ear drops containing aminoglycosides and polymixins [64], but these may dramatically improve many cases of chronic otorrhoea which, if left untreated, may be prone to serious complications, including sensorineural deafness. The risk of ototoxicity appears to be very small [65] and MERFIELD et al [66] could find no evidence of sensori-neural hearing loss in 70 ears treated with drops containing potentially ototoxic drugs. The use of antibiotic drops combined with hydrocortisone is significantly more effective [67].…”
Section: Hospital Carementioning
confidence: 95%
“…However, Browning et al found the incidence of CSOM to be 1.9% in males and 1.2% in females. 10 A sex ratio of 1.3 to 1 was found by M.A Yaor et al in their study. 11 In our study, 70% cases belonged to rural population while 30% belonged to urban population.…”
Section: Discussionmentioning
confidence: 55%